The Experience of Men Whose Partners Have Postpartum Depression. (November 2019) - Ierardi, Janet A.; Fantasia, Heidi Collins; Mawn, Barbara; Watson Driscoll, Jeanne
BACKGROUND: The correlation of paternal depressive symptomatology to maternal postpartum depression can approach 50%. Paternal depression during a female partner's postpartum time period can include feelings of fear, confusion, frustration, anger, helplessness, and lack of support. There are only a few published studies that address the interaction between paternal and maternal mental health during the postpartum period.AIMS: The purpose of this study was to gain insight into the experiences of men whose partners had postpartum depression as a foundation for intervention and program development.METHOD: This qualitative study used a descriptive phenomenological approach. A purposive sample of 10 men who lived with a partner diagnosed with postpartum depression was recruited via flier postings in mental health clinics, a perinatal mental health email listserv, and word-of-mouth. Single, audiotape-recorded interviews were completed. Qualitative data analysis was used to reduce initial coding to final themes that described participant experiences.RESULTS: The participants described efforts to provide support and care for their families; their efforts not to make things worse; their fears, anxieties, and physical responses; and the isolation associated with not knowing how to ask for help. The five themes included needing to support partners, maintaining stability, experiencing mutual symptoms, feeling isolated, and providing insight for others.CONCLUSIONS: Depression is known to have a negative effect on all members of a family. It is imperative that fathers' experiences are understood in order to fill this gap in caring for families.